A Fundamental Review on Candidate Processes for Robotic Process Automation (RPA) at Operational Level - Mohd Fakhri, Mat Saad; Chua, Yoon Chen; Hiew, Sir Loon; Aziz Hasan, Hossain; Abubakar, Hamisu Shira; Nyamupanemunda, Larry (INTI International University, 2020)
Digitalization has transformed the way organizations run its routine business activities. Emerging digital tools are increasingly prevalent and these tools have substantial prospect to drive for enhance organizational operational efficiency and performance. Organizational operations are supported by Business Process Management (BPM) – which the automation capabilities are central in facilitating the competitive advantage of modern businesses. A prevalent theme in modern BPM is Robotic Process Automation (RPA). Through RPA approach, organizations can steer their ability to improve overall efficiency, qualitatively and quantitatively. This paper provides a fundamental exploratory study on RPA with a general overview, related techniques and approaches for RPA implementations, RPA applications existed in current business process and recognized improvements driven by RPA. Consequently, a summative outline of business operational functions relative to candidate of RPA applications is presented as an essential guide. The outlines and recommendations would be able to serve and assist practitioners who are venturing into RPA approach to be more oriented on the planning, assessing and deciding the candidate processes for RPA implementation.